(3LGeY GdeMGSfs - (3CMeO Hf eMeO Hf Ydqj, pTgGH GdOjf GHf GdYWGQ, GdoqOnfrjnSQj,J (B794 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3EfeG Sej GdcJGH cJGHG dGLJeGY GdMQha hcPdc Sej GdYScQ cJjHI dGLJeGY GdLfO, bGd GdLGMX GdcJGH hYGA edF hXQa MTi XQaG s
(3BNQgG (B:s
(3gPG GdHjJ aj GdYjfj(B: (3heMSf Ef CMSf bhdG hYedG jPcQ Ef bGd, hjfSi Ef aYd s
(3GdJUhjQ eYJe aj Chd GdUaMGJ hBNQgGs
(3LeY ajg fHPkG ef cdGe GdHdZGA hcJGHGJge hfHPkG ef JGQjN GdCfHjGA hGdNdaGA hGdedhc hfhOGQ ef GdbUU hGdCNHGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B227 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B572s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs